Charcot’s foot reconstruction with removal of the navicular and cuboid bones plus arthrodesis of the medial and mid columns using two solid intramedullary fusion bolts—a case report - Mónico, José Lito (2021)
Charcot neuroarthropathy is a progressive chronic destructive arthropathy which can result in severe foot deformity, recurrent plantar ulceration, osteomyelitis and, ultimately, foot amputation. Treating a Charcot’s foot and preserving or restoring foot’s anatomy can be challenging. Several treatment methods have been previously described but they are associated with high rates of failure or adverse events. We report a clinical case of a 47-year-old patient with Charcot’s foot. Clinical examination and convectional radiography revealed a rocker bottom deformity with plantar ulceration. Plantar ulceration was addressed first with medical treatment, followed by surgical reconstruction and arthrodesis of the foot. In our case, we describe the advantages of complementing surgical treatment with medical treatment using a cast immobilization. Additionally, we describe our surgical reconstruction method with removal of the navicular and cuboid bones plus arthrodesis of the medial and mid columns, using two solid intramedullary fusion bolts, and stabilization of the lateral column with one Kirschner wire. We were able to successfully reconstruct foot’s anatomy and achieve a stable foot arthrodesis. During 12-month follow-up, no adverse medical events or screws breakdown were recorded. The patient is able to wear shoes again and walk in full weight bearing without limitations. Charcot’s foot surgical reconstruction should be done in non-acute inflammatory phase and achieve foot arthrodesis with rotational stability. Extended fixation of the medial and mid foot columns, with intramedullary solid fusion bolts, is mandatory to build a stable construct. Bone graft augmentation and full contact plastered boot in the first 3 postoperative months can provide additional stability.